Nivel de conocimiento sobre la alimentación cariogénica y no cariogénica en mujeres embarazadas de la parroquia rural Manú del cantón Saraguro, provincia Loja, periodo octubre 2021-marzo 2022 - Condolo Torres, Juleydi Viviana (2022)
Nutrition during pregnancy plays a particularly relevant role in the evolution of the future baby since the maternal organism initiates a series of physiological, biochemical, and metabolic processes of adaptation to ensure maternal and fetal health and that of the newborn. However, the lack of knowledge about healthy nutrition during pregnancy brings as a consequence a series of oral pathologies, among them caries, gingivitis, and periodontitis, a significant health problem in the Manú parish, Saraguro canton, Province of Loja. The objective of this descriptive, comparative, and cross-sectional study; is to determine the level of knowledge about cariogenic and non-cariogenic food to identify the type and frequency of consumption of cariogenic and non-cariogenic food and to educate and motivate pregnant women regarding the type of food they eat. Two validated surveys were administered to 12 pregnant women, consisting of 9 multiple-choice questions, with the prior acceptance of informed consent; the data were processed in the statistical program SPSS (Statistical Package for the Social Sciences) using the criterion of the correct answer applying the Likert scale (<5 Poor, 6 Acceptable, 7 Good Level, 8 Very Good Level, 9 Excellent). We obtained the following results: before the application of the education program, there was 100% of insufficient knowledge, and after the program, there was an increase in the level of understanding to 50%; the most frequent type of food was non-cariogenic in 58.3%, while cariogenic was present in 41.7%. In conclusion, the education program for pregnant women was successful since it increased the degree of familiarity with cariogenic and non-cariogenic diets, with a significant difference, with a p-value of 0.000298. Keywords: pregnancy, nutrition, caries, cariogenic diet.